Subacute Subdural Hematoma in a Patient with Bilateral DBS Electrodes - Ha Son Nguyen; Peter A. Pahapill (Case Reports in Neurological Medicine)
Subdural hematomas (SDH) in patients with implanted deep brain stimulating (DBS) electrodes are rare. Only a handful of cases have been reported in the literature. No clear management guidelines exist regarding the management of the hematoma and the existing electrodes. We describe a 68-year-old female with bilateral DBS electrodes, who presented with acute, severe hemiparesis due to a large subacute SDH with associated electrode displacement. Urgent hematoma evacuation reversed the hemiparesis; the electrodes were left undisturbed. Brain reexpansion occurred promptly. The patient was able to benefit from stable DBS therapies within 3 weeks of hematoma evacuation, maintained at 1.5-year follow-up. The case highlights that despite relative electrode migration due to a subdural hematoma, the electrodes may not require revision during initial hematoma evacuation or in a delayed fashion. Timely hematoma evacuation, coupled with brain reexpansion, may be adequate for the electrode to travel back to its original position and effect reasonable DBS therapies.